Al-ASMA’ Al-HUSNA-BASED INTEGRATED LEARNING IN THE EARLY CHILDHOOD CHARACTER BUILDING EDUCATION - Bahar, Herwina (Tawazun: Jurnal Pendidikan Islam, 2018)
This study showes that al-As a’ al-Husnacan be applied in the character building of the children. There are 10 characters taught in the early childhood education, i.e. love the Creator, polite, respecting others, generous, caring to environment, patient/low-profile, discipline, being responsible, independent, and creative. These characteristics should be applied early to children since in this stage they are in the appropriate ages to be introduced to the values of monotheism. These children are having high curiousity of Allah’s existence.Among 10 integrated learning models proposed by Robin Fogarty, 3 of them are considered effective to be implemented to under-aged learners, i.e. Connected, Webbed and Integrated. These models are student-centred, behaviorist, flexible, and centred of interest. Al-As a’ al-Husna-based Integrated Learning is designed suitable with the development stages of those under-aged learners. In this process, they will know and memorize al-As a’ al-Husna while they are discussing the theme of the lesson so that al-As a’ al-Husna will be blent to their personalities. Educating under-aged learners means preparing them as generations in golden future life. The values of faith should be given and taught to them as early as possible in order to protect them from the waves of globalisation and technology contradicted to Islamic norms and moral. An appropriate teaching model will become essential investment for their future. Keywords : Integrated Learning, al-As a’ al-Husna, Character Education